Consciousness and emotion. ERP modulation and attentive vs. pre-attentive elaboration of emotional facial expressions by backward masking - Michela Balconi (Neuropsychological Trends, 2008)
Attentive and pre-attentive facial stimulus processing is an important topic to explain how people comprehend affective disposition in others. The effect of perceived but not consciously elaborated emotional facial expression was explored in the present research. Secondly, we considered whether ERP can index unconscious mental process of emotion elaboration by using backward masking procedure. Pictures presenting a happy, sad, angry, fearful, disgusted, surprised expressions were submitted to twenty one subjects in both attentive and pre-attentive conditions. The two processes seem to be similar in their nature, since they are marked by analogous peak deflections. Two ERP effects were found, a positive (P300) deflection, maximally distributed on the parietal regions, and a negative (N200) deflection, more localized on the frontal sites. Nevertheless, some differences were found in terms of quantitative modulations of the two peaks. The N200 effect, ampler in attentive condition, may be considered such as an index of conscious processing of emotional faces, whereas the P3 (P3a) effect, higher in pre-attentive condition, was considered a specific marker of the automatic, unconscious process during the emotional face comprehension. The semantic significance of unconscious elaboration and the emotional type effect, as a function of arousal and valence, were discussed.